Prevention of Postprandial Hyperglycemia by Ophthalmic Nanoparticles Based on Protamine Zinc Insulin in the Rabbit - Saori Deguchi; Fumihiko Ogata; Takumi Isaka; Hiroko Otake; Yosuke Nakazawa; Naohito Kawasaki; Noriaki Nagai (MDPI AG, 2021)
Postprandial hyperglycemia, a so-called blood glucose spike, is associated with enhanced risks of diabetes mellitus (DM) and its complications. In this study, we attempted to design nanoparticles (NPs) of protamine zinc insulin (PZI) by the bead mill method, and prepare ophthalmic formulations based on the PZI-NPs with (nPZI/P) or without polyacrylic acid (nPZI). In addition, we investigated whether the instillation of the newly developed nPZI and nPZI/P can prevent postprandial hyperglycemia in a rabbit model involving the oral glucose tolerance test (OGTT). The particle size of PZI was decreased by the bead mill to a range for both nPZI and nPZI/P of 80-550 nm with no observable aggregation for 6 d. Neither nPZI nor nPZI/P caused any noticeable corneal toxicity. The plasma INS levels in rabbits instilled with nPZI were significantly higher than in rabbits instilled with INS suspensions (commercially available formulations, CA-INS), and the plasma INS levels were further enhanced with the amount of polyacrylic acid in the nPZI/P. In addition, the rapid rise in plasma glucose levels in OGTT-treated rabbits was prevented by a single instillation of nPZI/P, which was significantly more effective at attenuating postprandial hyperglycemia (blood glucose spike) in comparison with nPZI. In conclusion, we designed nPZI/P, and show that a single instillation before OGTT attenuates the rapid enhancement of plasma glucose levels. These findings suggest a better management strategy for the postprandial blood glucose spike, which is an important target of DM therapy.